Principles of Religious Moderation in Islamic Religious Education: An Exegesis of QS. Al-Ma’idah Verse 8 - Farhan Ferdino, Muhammad; Fakhriah, Nyimas; Yudistira Nugraha, Muhamad; Azzahra, Radhita; Razzaq, Abdur (Corolla International Conference, 2024)
The purpose of this study is to understand the principles of religious moderation in Islamic Religious Education (PAI) learning, beginning with its concept, challenges, and exegesis studies, and concluding with its principles as related to Al-Maidah verse 8. The purpose of this research is to obtain a qualitative approach, focusing on descriptive data analysis of observed a texts, with data derived from Qur’anic exegesis, relevant books, and journals on moderation. The data are then analyzed using descriptive analysis techniques. The results of this research show that, the religious moderation seeks to instill the values of justice, based on the Qur’an and Hadith, into Islamic Religious Education learning. This aims to create PAI learning that prioritizes the values of moderation, tolerance, and justice in fostering a balanced life (tawazzun), uprightness (i’tidal), tolerance (tasammuh), egalitarianism (musawwah), and deliberation (syura) in society and national is life. Therefore, Al-Maidah verse 8, when integrated into the concept of religious moderation in Islamic Education learning basiccaly, will be underscores the need for justice to prevent discrimination in learning processes. Islamic Education Learning, its learning will proceed effectively, peacefully, and harmoniously if the principles of religious moderation are applied, encompassing all aspects of the learning components themselves.